Real‐world data on incidence, clinical characteristics and outcome of patients with macrofocal multiple myeloma (MFMM) in the era of novel therapies: A study of the Greco‐Israeli collaborative myeloma working group. Issue 5 (2nd March 2020) - Katodritou, Eirini; Kastritis, Efstathios; Gatt, Moshe; Cohen, Yael C.; Avivi, Irit; Pouli, Anastasia; Lalayianni, Chrysavgi; Lavi, Noa; Delimpasis, Sosana; Kyrtsonis, Marie‐Christine; Michael, Michalis; Suriu, Celia; et al.
Abstract: We investigated incidence, characteristics and outcome of patients with macrofocal multiple myeloma (MFMM) treated mainly with novel therapies. Based on definition (BMPCs <20% and lytic lesions/plasmacytomas, without anemia, renal insufficiency or hypercalcemia) we identified 140 patients with MFMM, among 4650 myeloma patients (3%). Twice the number of patients with typical myeloma were used as controls; 60% were <65 years and 70% had advanced bone disease. Plasmacytomas were more frequent in MFMM compared with standard myeloma (68% vs 15%, P < .05). Adverse prognostic parameters (high lactate dehydrogenase, advanced stage, high risk cytogenetics, immunoparesis) were less common in patients with MFMM compared with controls ( P < .05); 90% received novel agents and 47% underwent autologous transplantation upfront; 90% achieved an objective response; 70% had at least very good partial response which was significantly higher compared with controls ( P < .05). After a median follow‐up of 52 months, 33 patients have died. Early death (<12 months) was infrequent in MFMM. Median progression‐free survival and overall survival (OS) were 46 and 129 months respectively, both significantly longer compared with controls ( P < .001). Proteasome inhibitor (PI)‐based therapy was the only independent predictor for OS in the multivariate analysis (HR: 3.9; P < .001). In conclusion, MFMM is a distinct entity presented in young and elderly subjects, characterized by limited bone marrow infiltration, advanced bone disease and frequent presence of plasmacytomas; MFMM patients have less often adverse prognostic features and achieve excellent responses and prolonged OS especially when treated with PI‐based therapies. Novel imaging will help in a more accurate classification of this entity.